Arlene A. Teraoka: The Silence of Entropy or Universal Discourse: The Postmodernist Poetics of Heiner Müller - Herbert A Arnold (GDR Bulletin, 1988)
New York: Peter Lang, 1985. (New York University Ottendorfer Series. Neue Folge, 21), 240 p.